(3bfhGJ GdJhRjY (B:s (3hXGFa GdJhRjY, GdhSWGA, efGaP GdJhRjY (B/s - (3ZdGH, fYjeIs ((3GdLRGFQ (B: s (3OGQ GdgOi ddWHGYI hGdfTQ hGdJhRjY(B, s, 2013)
(3jVe GdJhRjY, bfhGJ Ch efGaP GdJhRjY, bfhGJ hGSJQGJjLjGJ GdJhRjY, GdJSjjQ GdOGNdj dbfhGJ GdJhRjY, efGaP GdJhRjY heJZjQGJ GdSdhc, GdCOGA aj efGaP GdJhRjY, GdSdWI aj efGaP GdJhRjY, GdUQGY, GdfeGPL GdSdhcjI aj efGaP GdJhRjY(B.s
(3HjHdjhZQGajG(B: (3U U(B.161-175s